Pengaruh Motivasi, Beban Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT XYZ - Nazwa Shyreen Alieviandy; Muhammad Asif Khan; Eri Bukhari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine and analyze the effect of motivation, workload and work environment on employee performance. The research method used in this research is quantitative. The object of this research is 126 employees of PT XYZ. The data analysis method used in this research is Partial Least Square (PLS). The results showed that motivation has a positive and significant effect on the performance of PT XYZ employees with an original sample value of 0.464 and T-Statistic 7.416> 1.96. Workload has a positive and significant effect on employee performance of PT XYZ with an original sample value of 0.228 and T-Statistic 3.892> 1.96. The work environment has a positive and significant effect on the performance of PT XYZ employees with an original sample value of 0.323 and a T-Statistic of 6.163> 1.96.